1959
DOI: 10.1037/h0046855
|View full text |Cite
|
Sign up to set email alerts
|

Interest patterns of a group of high-ability, high-achieving students.

Abstract: This study investigates three problems which are significant in understanding the nature of vocational interests and in using the Strong Vocational Interest Blank in educational settings. The first concern is with the nature of interest patterns of high-ability students. How many types of patterns occur and in what areas are they found? Are interest patterns of such students different from those of a more heterogeneous group of college students?Reviews (Darley & Hagenah, 1955;Strong, 1943;Strong, 1955, Super, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1960
1960
1985
1985

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Gifted students also tend to have a more intrinsic motivational orientation than average intelligence students. For example, several authors report that gifted students have a wider range of interests that they pursue more actively than average intelligence students (Cox, 1926;Hildreth, 1966;Lehman, 1953;Martinson, 1973;Newland, 1976;Stewart, 1959). Others report that gifted students tend to prefer making their own decisions about what to study (Bachtold,1969;Lucito, 1964;Smith, 1962;Warren & Heist, 1960).…”
mentioning
confidence: 93%
“…Gifted students also tend to have a more intrinsic motivational orientation than average intelligence students. For example, several authors report that gifted students have a wider range of interests that they pursue more actively than average intelligence students (Cox, 1926;Hildreth, 1966;Lehman, 1953;Martinson, 1973;Newland, 1976;Stewart, 1959). Others report that gifted students tend to prefer making their own decisions about what to study (Bachtold,1969;Lucito, 1964;Smith, 1962;Warren & Heist, 1960).…”
mentioning
confidence: 93%
“…Numerous studies have demonstrated the effectiveness of the Strong Vo-RONALD G. TAYLOR [2] found that students of equivalent ability enrolled in the college of liberal arts and engineering had widely different interest patterns. Stewart [3] concluded that high ability students had highly similar interest patterns. Berdie [1] examined the scores on specific SVIB scales of graduate school physicians, lawyers, and business administration students and found that several scales did differentiate even though the test was administered in the senior year of high school.…”
mentioning
confidence: 99%